Arta excesului și a compromisului - Boantă, Adriana (Theatrical Research, 2021)
Art of Excess and Compromise An investigation of the codependent relationship between the work-author-commanditaire and its implications circumscribed to the „new order“, imposed by the grid of values established by the political-cultural context during the communist totalitarian regime.